THE RELATIONSHIP BETWEEN VEGETABLE AND FRUIT CONSUMPTION AND THE INCIDENCE OF ASTHMA IN CHILDREN AGED 13-14 YEARS - Manuhutu, Dave Christopher; Mestika Mayangsari, Ayu Setyorini; Pratiwi, I Gusti Ayu Putu Eka; Witarini, Komang Ayu (E-Jurnal Medika Udayana; Vol 14 No 01 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i1.P18, 2025)
Asthma is a chronic inflammatory disorder of the respiratory tract. Oxidative stress is one of the causes of the inflammatory process in the airways of children with asthma. Oxidative stress can be reduced with antioxidants. The role of antioxidants in vegetables and fruits has not yet received attention in the management of asthma in children. The aim of this study is to determine the relationship between the consumption of vegetables and fruits and the occurrence of asthma in in children aged 13-14 years. The research was conducted using an observational analysis with a cross-sectional study approach. A total of 236 students were selected as research subjects using stratified random sampling techniques. Data were collected through direct questionnaire filling at Tunas Daud Junior High School and State Junior High School 10 in Denpasar. The results showed that 83 students had insufficient vegetable consumption and 153 students had sufficient vegetable consumption. The occurrence of asthma in children with sufficient vegetable consumption was 16.3%, whereas in children with insufficient vegetable consumption, it was 47%. 77 students had insufficient fruit consumption and 159 students had sufficient fruit consumption. The occurrence of asthma in children with sufficient fruit consumption was 15.1%, whereas in children with insufficient fruit consumption, it was 51.9%. The prevalence ratio of asthma in children with sufficient vegetable consumption was 4.5 (95% CI 2.5-8.3; p<0.001) and in children with sufficient fruit consumption, it was 6.1 (95% CI 3.3-11.3; p<0.001). The conclusion of this study is that there is a relationship between the consumption of vegetables and fruits and the occurrence of asthma in children aged 13-14 years.   Keywords : Asthma, Vegetable and Fruit Consumption, Junior Hh School Students, Ages 13-14 Years